Alternative Techniques of Teaching and Learning in Brazilian Information Systems Courses: A Glimpse from Students and Teachers - Classe, Tadeu Moreira de; Castro, Ronney Moreira de; Castro, Cátia C. Carnevalli De (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Today’s digital society requires various skills like critical thinking, problem-solving, and decision-making. Educational processes must align with these skills and real-world situations, fostering reflective thinking and knowledge-building in students. Problem: Despite the crucial role of information systems (IS) courses for people in the technology information job market, many students exhibit low motivation in their classes, often caused by traditional teaching approaches. Solution: In this sense, this article explores the perceptions of teachers and students about conventional and alternative teaching methods in disciplines of Brazilian IS courses. Method: Our research employs survey-based steps. IS Theory: We used grounded theory and count methods as qualitative data analysis approaches. Summary Results: Findings highlight the use and impact of traditional and alternative techniques in IS courses, providing insights into teaching methodologies, learning processes, and student motivation. Contributions to IS: The research contributes to the information systems field, offering insights into teaching practices in Brazilian courses and suggesting strategies for enhancing IS education in the country.